2007
DOI: 10.1002/hbm.20425
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dyslexia: Gray matter abnormalities in the occipitotemporal cortex

Abstract: Functional neuroimaging studies have consistently demonstrated less activation of the left occipitotemporal cortex in dyslexic readers. This region is considered critical for skilled reading and damage to it in adult readers leads to severe deficits in reading ability. In contrast to these findings, structural abnormalities in the occipitotemporal cortex were not consistently found to date. We used optimized Voxel Based Morphometry with T1 weighted MR images to investigate gray matter volume in 13 dyslexic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
129
4
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(147 citation statements)
references
References 76 publications
(168 reference statements)
11
129
4
3
Order By: Relevance
“…Differences in non-cortical regions included the hippocampus/parahippocampus, amygdala, globus pallidus and putamen. These brain regions correlate with areas identified previously as being involved in reading and/or symbol decoding either structurally or functionally (Kronbichler et al 2007;Brambati et al 2006;Cao et al 2006;Casanova et al 2005;Silani et al 2005;Vinckenbosch et al 2005;Aylward et al 2003;Eckert et al 2003;Ruff et al 2003;Brown et al 2001;Eliez et al 2000;Rumsey et al 1999). …”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Differences in non-cortical regions included the hippocampus/parahippocampus, amygdala, globus pallidus and putamen. These brain regions correlate with areas identified previously as being involved in reading and/or symbol decoding either structurally or functionally (Kronbichler et al 2007;Brambati et al 2006;Cao et al 2006;Casanova et al 2005;Silani et al 2005;Vinckenbosch et al 2005;Aylward et al 2003;Eckert et al 2003;Ruff et al 2003;Brown et al 2001;Eliez et al 2000;Rumsey et al 1999). …”
Section: Discussionsupporting
confidence: 74%
“…More specifically, these studies show increases in GM volume in several cortical areas pertaining to language including: posterior, medial and inferior temporal gyri, precentral and postcentral gyri, superior and medial frontal gyri and precuneus (Kronbichler et al 2007;Silani et al 2005;Vinckenbosch et al 2005). These new data suggest that gray matter changes observed in dyslexia are not merely associated with decreases in gray matter alone and have a more complex genetic etiology.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Furthermore, most studies using diffusion tensor imaging (Beaulieu et al, 2005;Deutsch et al, 2005;Klingberg et al, 2000;Niogi and McCandliss, 2006) and voxelbased morphometry (VBM) (Eckert et al, 2005;Silani et al, 2005) have associated dyslexia with changes in anatomical connections of temporo-parietal regions. To date, only one VBM study found reduced gray matter density in the left inferior occipitotemporal cortex in adults and adolescents with dyslexia (Kronbichler et al, 2008). Accordingly, specifically designed studies combining techniques for examining A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Voxel-based morphometry reveals differences in gray-matter volume indices in individuals with DD (compared with typical reading controls) in various areas of the brain, including left occipitotemporal and temporoparietal areas (44,(56)(57)(58)(59)(60)(61), bilateral fusiform (59), and lingual gyrus (LG) (58) as well as the cerebellum (56-58). Morphological abnormalities in these regions can be identified even before reading skills are present in children as young as 5 to 6 y of age, suggesting atypical early development or even a genetic basis for DD (62).…”
mentioning
confidence: 99%